Biodiversity patterns in a macroinvertebrate community of a temporary pond network. Issue 1 (22nd March 2013) - Florencio, Margarita; Díaz‐Paniagua, Carmen; Gómez‐Rodríguez, Carola; Serrano, Laura; Tsubaki, Yoshitaka; Sahlen, Goran
Abstract Macroinvertebrate assemblages of temporary ponds are ideal model systems to explore biodiversity patterns and metacommunity ecology. In addition, the study of the environmental variables driving such biodiversity patterns is essential in establishing proper guidelines for the conservation of the singular fauna of temporary ponds, especially since such ponds are vulnerable systems. We analysed the macroinvertebrate assemblages and environmental characteristics of 80 ponds spread across the Doñana National Park, SW Spain to (i) analyse macroinvertebrate β‐diversity and metacommunity structure; and (ii) discern the main environmental and spatial drivers of these patterns. The pond network was highly heterogeneous as temporary ponds were highly variable. Macroinvertebrate β‐diversity partitioning showed that species replacement made the greatest contribution to total β‐diversity while the contribution of nestedness was small. The macroinvertebrate community structure and β‐diversity were similarly driven by: electrical conductivity (and co‐variables alkalinity, pH, and ion concentrations), plant richness (and the co‐variable pond surface area), maximum depth, marsh, and coastal proximity as well as two spatial descriptors extracted from Moran's eigenvector maps. The spatial descriptors indicated that large interpond distances were involved, suggesting that species dispersal limitations only take place over long distances in the area. Those taxa that departed from the general nested pattern, termed idiosyncratic, significantly contributed to the maintenance of high pond network diversity through the species replacement and occurred within particular environmental conditions in the pond network. These results reveal that environmental heterogeneity and connectivity are key factors in the preservation of high macroinvertebrate diversity in nested pond networks with high numbers of idiosyncratic species.